2017
DOI: 10.1108/ejmbe-10-2017-018
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based simulation in management and organizational studies: a survey

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 85 publications
(105 reference statements)
0
26
0
1
Order By: Relevance
“…The purpose of this study is to use agent-based modeling to simulate Bandura's triadic causation relationship between personal factors, behavioral patterns, and environmental events in the context of career occupation choices. Given that Bandura's model conceptualizes agency as a construct that emerges from the triadic causation model of interaction, agent-based modeling offers a suitable vehicle for simulation since the most distinctive feature of agent-based models (ABMs) is that they explicitly model interactions between different components (Gómez-Cruz Nelson et al 2017). Unlike other modeling tools, ABMs do not attempt to model system-wide properties.…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…The purpose of this study is to use agent-based modeling to simulate Bandura's triadic causation relationship between personal factors, behavioral patterns, and environmental events in the context of career occupation choices. Given that Bandura's model conceptualizes agency as a construct that emerges from the triadic causation model of interaction, agent-based modeling offers a suitable vehicle for simulation since the most distinctive feature of agent-based models (ABMs) is that they explicitly model interactions between different components (Gómez-Cruz Nelson et al 2017). Unlike other modeling tools, ABMs do not attempt to model system-wide properties.…”
Section: Purpose Of This Studymentioning
confidence: 99%
“…ABMs show how simple behavioral rules of agents and local interactions among them at a micro-scale can create surprisingly complex patterns at a macro-scale. This methodology has gained an increasing popularity, both in academia and industry such as the study of critical infrastructures dependence [22], consumption of services of sustainable eco-systems [23], economic sciences [24,25], and management [26,27]. For adoption and diffusion studies, a number of works have used ABM for studying the adoption and diffusion of technologies such as environmental technologies [28], energy technologies [29], health and medical technologies [30][31][32], agricultural technologies [33], cinema technologies [34], transportation technologies [35], electricity production [36], alternative fuels [37,38], organic farming practices [39], automobile markets [40], fuel cell vehicles [41,42], mobile phone [43], and smart metering [44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of flood risk management, agent-based models (ABMs) have been used to model evacuation strategies involving agents representing individual members of the public (Dawson, Peppe, & Wang, 2011;Liu, Okada, Shen, & Li, 2010). In addition, ABMs have been utilised to evaluate flood communication strategies on individuals (Haer, Botzen, & Aerts, 2016), analyse the influence of individual behaviour on community flood risk (Tonn & Guikema, 2017), investigate the role of individuals' use of social media in relation to flood evacuation (Du, Cai, Sun, & Minsker, 2017), assess individual household flood response preferences (Yang, Scheffran, Süsser, Dawson, & Chen, 2018) and examine the dynamic evolution of flood risk and vulnerability of homeowners (Dubbelboer, J., Nikolic, J., Jenkins, K., Hall, 2017;Jenkins, Surminski, Hall, & Crick, 2017) In terms of modeling businesses, a recent survey of the use of agent-based simulation in management and organizational studies revealed the highest number of applications being in the areas of operations and logistics, marketing and organizational behaviour (Gómez-Cruz, Loaiza Saa, & Ortega Hurtado, 2017). Beyond the areas reported in this survey, agent-based approaches have been used to study business related issues such as the dynamic formation of supply chains (Wang, Wang, Vogel, Kumar, & Chiu, 2009), cost collaborative management in supply chains (Fu & Fu, 2015) and the collaboration duration of supply chains (Arvitrida, Tako, Robertson, & Robinson, 2017).…”
Section: Modeling Smes' Flood Preparedness Response and Recoverymentioning
confidence: 99%